Problems and prospects of medical provision for military personnel with COVID-19 in the conditions of medical insurance - V. V. Trokhymchuk; I. O. Pankratov (Фармацевтичний журнал, 2023)
To date, the treatment of patients with COVID-19, which caused an unprecedented pandemic in 2019–2023, remains difficult. Military personnel of the Armed Forces of Ukraine during conscription, when returning from business trips and vacations (especially those who are in the incubation period or are asymptomatic) can bring COVID-19 into the unit and cause an outbreak of the disease.